Static longitudinal stability of a hybrid airship - ul-Haque, Anwar; Asrar, Waqar; Omar, Ashraf Ali; Sulaeman, Erwin; Syed Mohamed Ali, Jaffar (IEEE Computer Society, 2014)
Numerical simulations play a dominant role in design of experiments to get first hand knowledge about the aerodynamic behavior before the beginning of wind tunnel testing. In the present work, the static longitudinal stability characteristics of a single lobe winged-hybrid airship are investigated with two different empennages. Based on the previous computational and experimental work, numerical simulations are carried out by generating unstructured grids on scaled down geometry having ‘+ Type’ and a ‘inverted Y type’ empennage and by using SST turbulence model for specified flow conditions. The shape of the hull is a blunted spheroid-ellipsoid. The empennage arrangement is the only geometric dissimilarity in these two cases. Results obtained are first validated with the available experimental data. Numerical results show that for such low fineness ratio hull configurations, changing the tail configuration from ‘+ Type’ to ‘Inverted Y Type’ empennage has actually decreased the static stability at low speed. These initial numerical results will be useful for any future work related to the design of experiments with ‘Inverted Y Type’ empennage.